Accordo interistituzionale per l’anno accademico 2013/2014 programma LLP/Erasmus tra Università IUAV di Venezia e a Universidade Lusíada de Lisboa - Universidade Lusíada de Lisboa (2016)
- Cooperate for exchange of students and/or staff in the context of the Erasmus programme. - Subject area: Art and design.